Genomic Designing for Biotic Stress Resistant Pulse Crops 2022
DOI: 10.1007/978-3-030-91043-3_5
|View full text |Cite
|
Sign up to set email alerts
|

Tackling Lentil Biotic Stresses in the Genomic Era

Abstract: Lentils are already one of the main pulses of the world, as they are one of the main sources of protein for humans. As a crop, they are also gaining momentum because the rusticity and tolerance to water scarcity of some varieties are a good fit with the current global warming trend and climate change in general. However, while the harvested area and overall production have drastically increased over the last decades, yield has only experienced very modest increments. The reasons are two-fold. First, pathogens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 212 publications
0
1
0
Order By: Relevance
“…Studies have shown that virus epidemics is often due to high aphid populations that spread the virus during their short feeding periods. Surveys conducted in many countries around the globe during the last three decades demonstrated that significant limitation to legume production including lentil, is caused by aphid-borne viruses ( Pérez de la Vega et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that virus epidemics is often due to high aphid populations that spread the virus during their short feeding periods. Surveys conducted in many countries around the globe during the last three decades demonstrated that significant limitation to legume production including lentil, is caused by aphid-borne viruses ( Pérez de la Vega et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%